Development of a highly efficient p-coumaric acid-responsive biosensor in Saccharomyces cerevisiae - Xueqing Pang; Jingyuan Zhu; Yuqing Li; Jing Xiao; Xinyu Zhang; Depeng Ren; Pingping Zhou (Synthetic and Systems Biotechnology)
Developing biosensors to monitor and regulate intracellular biosynthesis pathways can significantly enhance natural product yields in microbial cell factories. This study created a novel biosensor in Saccharomyces cerevisiae to respond to p-coumaric acid, a critical precursor in the biosynthesis of polyphenols and flavonoids. This biosensor was constructed by expressing the BsPadR repressor from Bacillus subtilis and engineering hybrid promoters. Notably, the PBS1-CCW12 hybrid promoter exhibited tight regulation by BsPadR and enhanced activity in response to p-coumaric acid. However, excessive BsPadR expression negatively impacted yeast growth, which was mitigated by using weaker promoters, PBST1 and PERG9. Furthermore, the impact of nuclear localization signal (SV40-NLS) positioning on BsPadR functionality was explored, revealing that fusion of an SV40-NLS at the C-terminus of BsPadR enhanced the biosensor's performance. To validate its utility, we applied this system to dynamically regulate CrtE (geranylgeranyl pyrophosphate synthase), a key enzyme in lycopene biosynthesis. By coupling p-coumaric acid production with lycopene biosynthesis, we enabled high-throughput colorimetric screening for enzyme evolution and strain selection. This novel biosensor serves as a valuable tool for future studies aimed at optimizing the production of p-coumaric acid and its derivatives in S. cerevisiae, thereby advancing the efficiency of biosynthetic processes in microbial cell factories.